Sampling site and potential errors in estimating total body water and water turnover rate in fasting hooded seals (Cystophora cristata) - Alvira-Iraizoz, Fernando (UiT Norges arktiske universitet, 2014)
The purpose of this project is to study in detail the water balance and methodological aspects of the use of the tritiated water method of hooded seals (Cystophora cristata). Following 24 hours of fasting, 5 sub-adult hooded seals aged 1.5 years were injected intravenously with a bolus dose of tritiated water through a catheter inserted into the extradural intravertebral vein (EDV) at the level of the lumbar vertebra. A second catheter was inserted at a lower level of the EDV and blood samples collected from both at different intervals. An additional blood sample was collected from the femoral vein. The seals were then reintroduced into seawater and fasted for a period of 4 days. At the last day of the experiment blood samples were collected from a catheter inserted into the EDV and from the femoral vein. The specific activity (SA) in plasma samples was measured to assess if there were any differences between the sampling sites. Total body water and turnover rate were determined according to the dilution rate of tritiated water over time. No statistical differences were shown between the 2 catheters in EDV. However, differences between samples from the femoral vein and EDV occurred in 2 of the seals. Total body water decreased on average (n = 5) 1.2 ± 0.1 l during the experimental period. Total rate of efflux was 2035 ± 145 ml • day-1 with a daily net water loss of 297 ± 15 ml. All the seals showed a large extent of mariposia during the 4 days of fasting (1147 ± 153 ml • day-1). It is concluded from this study that sampling site does not affect the SA of 3H2O in plasma. However, the use of a second catheter is strongly recommended to be sure to avoid any contamination. In addition, it is concluded that sub-adult, fasting hooded seals drink seawater to a significant extent.